“A Mission and Purpose to Make Some Sense out of Everything That Was Happening to Me”: A Qualitative Assessment of Mentorship in a Peer-to-Peer Gynecologic Cancer Program - Moran, Hannah Kang; Spoozak, Lori; Brooks, Joanna Veazey (Journal of cancer education, 2024)
This study aimed to elucidate the relationship between mentorship, survivorship, and identity construction in people who have had gynecologic cancer and participated as mentors in a peer mentorship program. A qualitative descriptive study was designed, and hour-long semi-structured interviews with peer mentors were conducted. Interviews investigated how serving as a peer mentor influenced understanding of mentors’ own cancer experiences. Thematic analysis was then conducted. All authors open-coded a subset of interviews to develop a codebook, which was then used to code the remaining transcripts. This qualitative inductive analysis of over 7 h of data was managed with NVivo 12. Seven peer mentor participants ( N = 7) were interviewed. Four main themes emerged: serving in the social role of mentor gave participants (i) a sense of daily direction in their lives, (ii) an opportunity to give back to others in the cancer community, (iii) an explanatory reason for their cancer journey, and (iv) the ability to reify their own status as survivor. Providing support through a peer mentorship program helped our participants make meaning in their own cancer experience.